2017
DOI: 10.1038/s41598-017-09058-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of inflammation-related gene expression in endothelial cells activated by complement MASP-1

Abstract: Mannan-binding lectin-associated serine protease 1 (MASP-1), the most abundant enzyme of the complement lectin pathway, is able to stimulate human umbilical vein endothelial cells (HUVECs) to alter the expression of several cytokines and adhesion molecules. This study has assessed to what extent MASP-1 is able to modify the transcriptional pattern of inflammation-related (IR) genes in HUVECs. We utilized Agilent microarray to analyse the effects of recombinant MASP-1 (rMASP-1) in HUVECs, on a set of 884 IR gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Moreover, MASP-1 treatment increased adhesion between neutrophils and endothelial cells by upregulating E-selectin expression in human umbilical vein endothelial cells (HUVECs) ( 98 ). A genome-wide gene expression profiling study on HUVECs corroborated the role of MASP-1 in triggering inflammation ( 99 ). The analysis showed that MASP-1 up- and downregulated numerous inflammation-related genes bridging complement activation and endothelial-cell-related inflammatory processes.…”
Section: Components Of Ap and Lp As Potential Drug Targetsmentioning
confidence: 85%
“…Moreover, MASP-1 treatment increased adhesion between neutrophils and endothelial cells by upregulating E-selectin expression in human umbilical vein endothelial cells (HUVECs) ( 98 ). A genome-wide gene expression profiling study on HUVECs corroborated the role of MASP-1 in triggering inflammation ( 99 ). The analysis showed that MASP-1 up- and downregulated numerous inflammation-related genes bridging complement activation and endothelial-cell-related inflammatory processes.…”
Section: Components Of Ap and Lp As Potential Drug Targetsmentioning
confidence: 85%
“…We have recently reported that in ECs, rMASP-1 regulates the expression of genes involved in the inflammatory reaction (29). Here we show that rMASP-1 treatment significantly changed the expression of 25 permeability-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA isolation and microarray processing were carried out as described in our earlier study (29). Briefly, confluent layers of HUVECs from four individuals were cultured in 6-well plates and treated for 2 h with 0.6 μM rMASP-1.…”
Section: Methodsmentioning
confidence: 99%
“…This activity (like that of kallikrein) enables the release of bradykinin, a highly pro-inflammatory mediator of the contact system. Furthermore, it was demonstrated that MASP-1 contributes to the pro-inflammatory activation of endothelial cells and increases endothelial permeability [ 82 , 83 , 84 ]. Recently, MASP-1 was reported to affect the transcription of alternative pathway factor D [ 85 ].…”
Section: Mbl-associated Serine Proteases (Masp) and Their Related mentioning
confidence: 99%